Manejo de plantas daninhas e seletividade de sistemas de controle químico para a cultura do algodão Liberty Link® - Franchini, Luiz Henrique Morais (2012)
Currently, most of Brazilian cotton is cultivated by large farmers, mainly in the Cerrado region. In the current cropping system, weed control is based on the use of different modalities of herbicide application. The present study was proposed to evaluate if the adoption of a pre-emergent application of herbicide would effectively affect the selectivity and weed control by post-emergent applications of ammonium glufosinate in Liberty Link (LL) cotton. Besides, it was addressed to compare weed management systems (with ammonium glufosinate or with conventional herbicides) in LL cotton. The results indicated that all combinations of herbicide treatments evaluated were selective to cotton. For LL management, use of three sequential post-emergence applications of ammonium glufosinate without previous pre-emergence application did not ensure maximum crop yield, although it provided a high level of weed control. Application of a pre-emergence herbicide eliminates early weed interference and decreases weed densities at post-emergence applications, what enables more flexibility in strategies for post-emergence weed control.